Attribute of Teacher according to Buddhism - Thangthongmadan, Sathien (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2019)
This Article is to study Attribute of Teacher according to Buddhism. There are three purposes : 1) to study the meaning of “teacher”, 2) to study the attribute of teacher according to Psychology and 3) to study the attribute of teacher according to Buddhism. From the study, it is found that The term "teacher" refers to a firm, stable person who has a love and good desire to pupils, who should be respected by students and general people. The Attribute of teacher according to Psychology consists of Cognitive characteristics. That is, independence in operations, conceptual level as a result of operations and Including analytical thinking. Affective characteristics consists of attitude, expectations, concerns and concerns. The Attribute of teacher according to Buddhism consists of three important reasons for namely: the teachers must have good knowledge in the subjects taught, to have good ability to transfer knowledge and the teacher must be exemplary for students